Air pollutants and hospital admissions due to cardiovascular diseases in Sao Jose do Rio Preto, Brazil - Cota Mantovani, Katia Cristina [UNESP]; Costa Nascimento, Luiz Fernando; Moreira, Demerval Soares; Ferreira da Silva Vieira, Luciana Cristina Pompeo [UNESP]; Vargas, Nicole Patto (Abrasco, 2016)
This study aimed to estimate the effects of environmental pollutants on the increase of hospitalizations due to cardiovascular diseases. This was an ecological study conducted in the city of Sao Jose do Rio Preto, Sao Paulo, Brazil, with data from hospital admissions with diagnoses in the categories of I-00 to I-99, from October, 1, 2011, to September 30, 2012. Fineparticulate matter (PM2,5), ozone, carbon monoxide, nitrogen oxide and nitrogen dioxide were the pollutants studied; they were estimated by CATT-BRAMs model. The use of an additive Poisson regression model showed association between exposure to PM2,5 and hospital admission due to cardiovascular diseases. In the fifth day after exposure to this pollutant (lag 5), the relative risk for hospitalization due to cardiovascular diseases increased 15 percent in according to 10 mu g/m(3) increase on PM2,5 concentrations. There were 650 avoidable hospital admissions and an excess of R$ 1.9 million in hospital expenses. Thus, it was possible to identify the association between exposure to PM2,5 and hospital admission due cardiovascular diseases in medium-sized cities, like Sao Jose do Rio Preto.
Keywords: Air pollutants; Particulate matter; Cardiovascular diseases; Hospital costs; Mathematical models